PENGARUH KEPEMILIKAN SAHAM, PROFITABILITAS, LEVERAGE, DAN OPINI AUDITOR TERHADAP AUDIT DELAY - Arumsari, Vivien Fitriana; Handayani, Nur (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
This research is meant to find out whether the influence of stock ownership, profitability, leverage, andauditor opinion to the audit delay on banking companies which are listed in Indonesia Stock Exchangein 2013-2015 periods. This research has been done by using purposive sampling method and appliedquantitative research. The data is the secondary data which is the financial statement of the companywhich has been obtained from www.idx.co.id. The samples are 33 companies with three observationperiods so 99 observation objects have been selected as observation objects. The independent variablesuses stock ownership, profitability, leverage, and auditor opinion to the audit delay. This research hasbeen done by using multiple linear regressions and statistics test the SPSS 20th version. Based on theresult of the research, it indicates that institutional ownership and profitability gives negative influencewhereas managerial ownership, leverage and auditor opinion does not give any influence to the auditdelay.Keywords: Stock ownership, profitability, leverage, auditor opinion, audit delay.